Electrification of the paper and pulp industry - Schnell, Sophie (2024)
This thesis addresses the urgent need to decarbonize global industries, responsible for over one-third of total energy consumption. Focusing on the Chemical, Cement, Iron and steel, and Paper & Pulp sectors, the study emphasizes the critical role of electrifying heat in industries to limit our climate footprint and reach sustainable goals. EDP emerges as a key player, committing to a sustainable future. Strategic partnership analyses explore EDP's role in catalyzing decarbonization efforts and helping industry electrify. The thesis provides concise insights into the challenges and opportunities, offering a strategic framework for sustainable industry electrification, with EDP at the forefront of this transformative journey.